Comparison of microwave pyrolysis and conventional pyrolysis of Eupatorium adenophorum. Issue 2 (25th August 2022) - Lin, Jin; Cheng, Song; Zhao, Saidan; Liu, Yongzhi; Xia, Hongying; Xing, Baolin
Abstract: Eupatorium adenophorum is used as the raw material to produce valuable pyrolysis products by microwave pyrolysis (MP). The influence of pyrolysis parameters (pyrolysis temperature, pyrolysis time and nitrogen flow rate) on the yield of pyrolysis products is investigated to get the optimal pyrolysis condition. Eupatorium adenophorum is also conducted in the conventional pyrolysis (CP) to investigate the influence of heat mechanism on the generation process of pyrolysis products. A comparison of MP and CP indicates that MP produces more bio‐gas (48.14%), and less bio‐oil (26.35%) compared to CP. The less carboxylic acid and more phenol in bio‐oil of MP are observed in the condition of MP compared to CP, indicating that MP could upgrade the quality of bio‐oil. Bio‐gas of MP has larger content of H2 and syngas (H2 + CO) than those obtained from CP. The property of bio‐char from MP is better than that of CP in terms of heat value, oxygen content, and specific surface area, which could be utilized in the metallurgical industry. Abstract :